Implementation of Discussion Actions on the Advantages and Disadvantages of Interacting with Others in Patients with Social Isolation in the Antareja Room of Dr. H. Marzoeki Mahdi Hospital, Bogor - Aja, Reni - (Akademi Keperawatan RSPAD Gatot Soebroto, 2021)
Social isolation is a condition where a person experiences or is unable to interact with other people around them. Signs and symptoms in patients with social isolation are characterized by signs of flat affect, sad affect, no enthusiasm/lethargy, no eye contact, no interest/refusing to interact with other people or the environment, withdrawing, feeling unsafe in public places, feeling preoccupied with their own thoughts. The purpose of implementing strategy 1 is to improve the ability to interact. Patients with social isolation need to be treated immediately because if not treated it can affect the entire patient system, especially the family and environment. The method in this case study is by describing the results of implementing discussion actions about the advantages and disadvantages of interacting with others. The interventions carried out were identifying the causes of social isolation and discussing with patients the advantages and disadvantages of interacting with others which were carried out for 3 days. The results of this case study showed that the implementation of strategy 1 could be resolved on the 3rd day. Based on the case study, it was found that the action of discussing the advantages and disadvantages of interacting with others is a good action to take for patients with social isolation because it can improve the ability to interact with others.